Institutions, informality, and influence: explaining nuclear cooperation in the Australia-US alliance. Issue 2 (2nd April 2020) - Frühling, Stephan; O'Neil, Andrew
ABSTRACT: Nuclear cooperation has been a consistent feature of the Australia-US alliance. In the 1950s and 1960s, Canberra explored transferring US nuclear weapons to Australian forces operating in Southeast Asia. Since the 1960s, Australian governments have supported hosting joint facilities that contribute to America's ability to execute global nuclear operations. And Australia has regularly invoked the nuclear umbrella as part of the alliance. We explain the key sources of nuclear cooperation in the alliance by leveraging realist and institutionalist theories of alliance cooperation. While realism explains limits to US nuclear commitments in the 1950s, institutional explanations are more relevant in pinpointing the sources of nuclear cooperation and in explaining why Australia has often achieved its policy preferences as the junior partner.